2014
DOI: 10.1111/echo.12508
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Rupture after Embolic Myocardial Infarction Due to Mitral Valve Endocarditis

Abstract: We report a very rare case of a 43-year-old patient with fatal left ventricular subepicardial aneurysm rupture complicating embolic myocardial infarction due to mitral valve infective endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…These factors hasten allograft degeneration, which can lead to structural dysfunction, creating an ideal environment for infection [39,128]. Similar conclusions were reached by researchers in Cleveland [31].…”
Section: Risk Of Allograft Infectionsupporting
confidence: 62%
See 1 more Smart Citation
“…These factors hasten allograft degeneration, which can lead to structural dysfunction, creating an ideal environment for infection [39,128]. Similar conclusions were reached by researchers in Cleveland [31].…”
Section: Risk Of Allograft Infectionsupporting
confidence: 62%
“…This can potentially cause complications such as stroke and left ventricular dysfunction. In cases of endocarditis involving the mitral valve, there may be dysfunction of the posteromedial papillary muscle with varying degrees of injury to the cords, which can lead to left ventricular rupture [30][31][32][33]. Various population-based reports have shown that patients who underwent surgery had an in-hospital mortality rate of 24%, while those receiving medical therapy had a rate of 26.4%.…”
Section: Introductionmentioning
confidence: 99%